(untitled) (International Journal of Child Health and Nutrition, 2016)
Background: To determine critical factors associated with severely malnourished children under five this case-control study was conducted. Methods: The data of a total of 433 children aged 0-59 months and admitted to the Hospital Yalgado Ouedraogo, (CHU – YO) between January 31, 2009 to January 31, 2013, were included in the analysis: 72 for the case group and 361 for the control group. Clinical and treatment records were accessed and data were analyzed. Results: For clinical signs, determinants of mortality were diarrhea [OR = 4.6; (95%CI 2.6-8.2], anorexia [OR = 2.7; (95%CI 1.4-5.0] and hepatomegaly [OR = 2.6; (95%CI 1.4-4.8]. For infections, determinants of mortality were pediatric HIV/AIDS [OR = 10.9; (95%CI 5.6-21.5] and digestive illnesses [OR = 5.1 (95%CI 2.8-9.4)]. Regarding the complications of malnutrition, determinants of mortality were severe dehydration [OR = 16.4 (95%CI 8.0-33.5)], skin lesions [OR = 14.3 (95%CI 6.4 -31.9)], heart failure [OR = 6.8 (95%CI 2.5-19.0)] and severe anemia [OR = 3.2(95%CI 1.4-7.1)]. For biochemical indicators, low serum sodium [OR = 0.7(95%CI 0.5-1.0)] and potassium levels [OR = 0.9(95%CI 0.9-1.0)] were the critical factors. In addition the risk of death was associated with low value of MUAC [OR = 0.9 (95% CI 0.8-0.9)]. Conclusions: The risk of death of children with severe acute malnutrition varies according to different factors studied.